Ventilatory variables and computed tomography features in COVID-19 ARDS and non–COVID-19-related ARDS: a prospective observational cohort study - Li-Chung Chiu; Hsin-Hsien Li; Yu-Hsiang Juan; How-Wen Ko; Scott Chih-Hsi Kuo; Chung-Shu Lee; Tien-Ming Chan; Yu-Jr Lin; Li-Pang Chuang; Han-Chung Hu; Kuo-Chin Kao; Ping-Chih Hsu (European Journal of Medical Research)
Abstract Background This study compared the ventilatory variables and computed tomography (CT) features of patients with coronavirus disease 2019 (COVID-19) versus those of patients with pulmonary non–COVID-19-related acute respiratory distress syndrome (ARDS) during the early phase of ARDS. Methods This prospective, observational cohort study of ARDS patients in Taiwan was performed between February 2017 and June 2018 as well as between October 2020 and January 2024. Analysis was performed on clinical characteristics, including consecutive ventilatory variables during the first week after ARDS diagnosis. Analysis was also performed on CT scans obtained within one week after ARDS onset. Results A total of 222 ARDS patients were divided into a COVID-19 ARDS group (n = 44; 19.8%) and a non–COVID-19 group (all pulmonary origin) (n = 178; 80.2%). No significant difference was observed between the two groups in terms of all-cause hospital mortality (38.6% versus 47.8%, p = 0.277). Pulmonary non–COVID-19 patients presented higher values for mechanical power (MP), MP normalized to predicted body weight (MP/PBW), MP normalized to compliance (MP/compliance), ventilatory ratio (VR), peak inspiratory pressure (Ppeak), and dynamic driving pressure (∆P) as well as lower dynamic compliance from day 1 to day 7 after ARDS onset. In both groups, non-survivors exceeded survivors and presented higher values for MP, MP/PBW, MP/compliance, VR, Ppeak, and dynamic ∆P with lower dynamic compliance from day 1 to day 7 after ARDS onset. The CT severity score for each of the five lung lobes and total CT scores were all significantly higher in the non–COVID-19 group (all p < 0.05). Multivariable logistic regression models revealed that Sequential Organ Failure Assessment (SOFA) score was independently associated with mortality in the COVID-19 group. In the non–COVID-19 group, body mass index, immunocompromised status, SOFA score, MP/PBW and total CT severity scores were independently associated with mortality. Conclusions In the early course of ARDS, physicians should be aware of the distinctions between COVID-19-related ARDS and non–COVID-19-related ARDS in terms of ventilatory variables and CT imaging presentations. It is also important to tailor the mechanical ventilation settings according to these distinct subsets of ARDS.